Does the COVID-19 Pandemic Disproportionately Affect the Poor? Evidence from a Six-Country Survey - Hai-Anh Dang; Toan L. D. Huynh; Manh-Hung Nguyen (Institute of Labor Economics (IZA), 2020)
The COVID-19 pandemic has wrought havocs on economies around the world. Yet, barely any evidence currently exists on the distributional impacts of the pandemic. We provide the first study that offers new theoretical and empirical evidence on the distributional impacts of the pandemic on different income groups in a multi-country setting. Analyzing rich individual-level data from a six-country survey, we find that while the outbreak has no impacts on household income losses, it results in a 65-percent reduction in the expected own labor income for the second-poorest income quintile. The impacts of the pandemic are most noticeable in terms of savings, with all the four poorer income quintiles suffering reduced savings ranging between 5 and 7 percent compared to the richest income quintile. The poor are also less likely to change their behaviors, both in terms of immediate prevention measures against COVID-19 and healthy activities. We also find countries to exhibit heterogeneous impacts. The United Kingdom has the least household income loss and expected labor income loss, and the most savings. Japanese are least likely to adapt behavioral changes, but Chinese, Italians, and South Koreans wash their hands and wear a mask more often than Americans.
Keywords: D00; H00; I1; I3; O1; 330; income quintiles; poverty; COVID-19; behavior changes